Technological prospection of Diminazene Aceturate, an Angiotensin II Converting Enzyme activator, in front of diarrheic disorders (Research, Society and Development, 2020)
Diarrhea, which is a gastrointestinal disease, has as its main characteristic the rapid passage of gastric contents through the intestine, which leads to the loss of water and electrolytes and consequent dehydration. The most common fluid replacement is the use of oral rehydration solution (ORS) together with the use of the drug loperamide. However, the use of this medication can cause severe bacteremia followed by sepsis and even death. Currently, there is no effective pharmacological treatment for diarrhea, therefore, it is noted the importance of seeking new therapeutic targets for the treatment of this disease. Thus, the aim of the present study was to conduct a research on the biological activities already described for Diminazene Aceturate with a special focus on antidiarrheal agents. For this, a survey was carried out, through patent filing searches, in the USPTO, EPO, WIPO and INPI databases, using keywords and Boolean operators. Thus, it was found in the international patent databases the number of documents referring to the use of Diminazene Aceturate in several areas, mainly in the pharmaceutical industry, but with a relatively low number of documents regarding the description of possible antidiarrheal action of the compound under study , which reinforces the innovative character of research involving the use of Diminazene Aceturate as an antidiarrheal agent.